2011
DOI: 10.1371/journal.pone.0014503
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Increase in TAG and DAG Content Parallel the Insulin Sensitizing Effect of Unilateral DGAT1 Overexpression in Rat Skeletal Muscle

Abstract: BackgroundThe involvement of muscle triacylglycerol (TAG) storage in the onset of insulin resistance is questioned and the attention has shifted towards inhibition of insulin signalling by the lipid intermediate diacylglycerol (DAG). The enzyme 1,2-acylCoA:diacylglyceroltransferase-1 (DGAT1) esterifies a fatty acyl-CoA on DAG to form TAG. Therefore, the aim of the present study was to investigate if unilateral overexpression of DGAT1 in adult rat Tibialis anterior (TA) muscle will increase conversion of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 48 publications
3
39
1
1
Order By: Relevance
“…However, we previously reported that elevated muscle DAG levels are not per se accompanied by skeletal muscle insulin resistance. That is, we showed that myocellular DGAT1 overexpression, an enzyme responsible for the conversion of DAG into inert TAG, improved skeletal muscle insulin sensitivity, yet increased muscle DAG levels (31). This phenomenon of improved insulin sensitivity coupled to increased storage of DAG in muscle was also reported in endurance-trained athletes (32).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, we previously reported that elevated muscle DAG levels are not per se accompanied by skeletal muscle insulin resistance. That is, we showed that myocellular DGAT1 overexpression, an enzyme responsible for the conversion of DAG into inert TAG, improved skeletal muscle insulin sensitivity, yet increased muscle DAG levels (31). This phenomenon of improved insulin sensitivity coupled to increased storage of DAG in muscle was also reported in endurance-trained athletes (32).…”
Section: Discussionsupporting
confidence: 74%
“…DAG Measurement. Total lipids were extracted from frozen mouse tibialis anterior muscle and DAG content was determined as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…However, our results clearly show substantial increases in both DAGs and ceramides, and yet no detriments to insulin signaling. This result is at first counterintuitive; however, other reports have found similar increases in lipotoxic species without induction of insulin resistance, including the well-known athlete's paradox (31)(32)(33)(34). Elevated DAGs have been found in endurance athletes with high insulin sensitivity (35).…”
Section: Discussionmentioning
confidence: 88%
“…Increasing net TG synthesis by diacylglycerol acyltransferase-1 (DGAT1) overexpression (70,106) or ATGL inactivation (34,59) promoted skeletal muscle insulin sensitivity. Conversely, isolated skeletal muscle from whole body DGAT1 knockout mice exhibited insulin resistance (70).…”
Section: A Case For Lipoexpediency In Skeletal Musclementioning
confidence: 99%